2020
DOI: 10.25115/ejrep.v18i52.3170
|View full text |Cite
|
Sign up to set email alerts
|

The effect of social deprivation and gender on self-efficacy beliefs about the postsecondary transition

Abstract: Introduction. High school students' self-efficacy beliefs about their ability to successfully obtain a first postsecondary destination in employment, education or training, and the learning sources of these beliefs were examined. Method. Factor analysis of an inventory administered to 1044 high school students (573 males and 471 females) who attended six urban schools identified five factors. Results. ANOVA indicated that students living in areas of higher deprivation reported significantly lower levels of pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
(55 reference statements)
1
2
0
Order By: Relevance
“…This result could potentially contribute to an explanation of why high school students from areas of greater social deprivation are at increased risk of failing in the postsecondary transition. It could be that this heightened perception of barriers in high school students from areas of greater social deprivation is associated with the lower self-efficacy beliefs about the postsecondary transition, which were reported by Douglas and Topping (2020) and Gonzalez et al (2013). It is also possible this heightened perception of barriers in high school from areas of greater social deprivation is resulting in lower career aspiration, which would be consistent with the findings of Kenny et.…”
Section: Career Barriers and Socioeconomic Statussupporting
confidence: 63%
See 2 more Smart Citations
“…This result could potentially contribute to an explanation of why high school students from areas of greater social deprivation are at increased risk of failing in the postsecondary transition. It could be that this heightened perception of barriers in high school students from areas of greater social deprivation is associated with the lower self-efficacy beliefs about the postsecondary transition, which were reported by Douglas and Topping (2020) and Gonzalez et al (2013). It is also possible this heightened perception of barriers in high school from areas of greater social deprivation is resulting in lower career aspiration, which would be consistent with the findings of Kenny et.…”
Section: Career Barriers and Socioeconomic Statussupporting
confidence: 63%
“…The CSM also hypothesises that individual differences in person factors such as socioeconomic status and gender are important variables witin the career development processes, and can have effects throughout the transmission pathways of the model (Brown and Lent, 2018). In an empirical, study Douglas and Topping (2020) confirmed that students living in areas of higher social deprivation, and females in particular, reported lower levels of self-efficacy belief that they could successfully obtain a place in employment or education after leaving school.…”
Section: The Social Cognitive Model Of Career Self-managementmentioning
confidence: 88%
See 1 more Smart Citation